Matching colors in jersey sponsorship: The effect of team-colored sponsor logo on jersey aesthetics and purchase intention - Sung Wook Son; Antonio Williams (Journal of Applied Sports Management, 2025)
In jersey sponsorship, some sponsors today have decided to modify their logo colors to match the team colors. The present research examined the role of team-colored sponsor logo in jersey sponsorship, paying particular attention to its impact on perceived aesthetics of the jersey and fans’ willingness to purchase. Three experiments using both fictitious and actual sponsors across two different sports showed that the team-colored sponsor logo on a jersey was a positive predictor for both perceived aesthetics and purchase intention at all levels of team identification. The findings also revealed the indirect effect of the team-colored sponsor logo on purchase intention via perceived aesthetics. The findings provide insights for both sponsors and teams to maximize jersey sponsorship outcomes for short- and long-term benefits.
Keywords: Jersey sponsorship; team-colored sponsor logo; jersey aesthetics; purchase intention